THE INFLUENCE OF THE FAMILY EDUCATIONAL PROCESS ON THE DEVELOPMENT OF A CHILD'S PERSONALITY (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article deals with issues related to the family environment and parental relationships in the upbringing of children. The article can be used by future specialists who are developing their intellectual potential associated with their professional activities.